Compact circularly polarized textile antenna - Ismail, Muhammad Faizal (2014)
The performance of a compact circular polarization (CP) textile antenna is presented. The design is based on the traditional CP rectangular truncated patch antenna. Four slits are introduced at every edge of the rectangular truncated patch antenna to make it compactness. Simulated results show that the proposed antenna can have an antenna reduction of about 18% compared to the traditional one. A good bandwidth (2.40 GHz – 2.50 GHz) with axial ratio (AR) bandwidth (2.41 GHz – 2.44 GHz) and gain of 5.70 dB is presented. This antenna is suitable for application of wireless monitoring communication system and Wireless Local Area Network (WLAN) application.